2021
DOI: 10.2188/jea.je20190210
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Habitual Sleep Duration and Mortality According to Sex and Age: The Japan Public Health Center-based Prospective Study

Abstract: Background: Short and long sleep durations are associated with mortality outcomes. The association between sleep duration and mortality outcomes may differ according to sex and age. Methods: Participants of the Japan Public Health Center-based prospective study (JPHC Study) were aged 40-69 years and had completed a detailed questionnaire on lifestyle factors. Sex-and age-stratified analyses on the association between habitual sleep duration and mortality from all-causes, cardiovascular diseases (CVD), cancer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…These sex-specific differences could be attributable to the association of sleep with cancer sites (eg, breast cancer). One possible reason for our discrepant findings compared with 2 large Japanese prospective studies, 28 , 29 of which 1 study 29 is included in the current analysis, is study size, indicating that large populations may be required to detect sex-specific associations between sleep duration and cancer mortality in East Asian populations. The absence of any association between sleep duration and cancer mortality in men in the multivariable model in the current study is explained entirely by the included covariates that abrogated the significant associations in the minimally adjusted model.…”
Section: Discussionmentioning
confidence: 94%
“…These sex-specific differences could be attributable to the association of sleep with cancer sites (eg, breast cancer). One possible reason for our discrepant findings compared with 2 large Japanese prospective studies, 28 , 29 of which 1 study 29 is included in the current analysis, is study size, indicating that large populations may be required to detect sex-specific associations between sleep duration and cancer mortality in East Asian populations. The absence of any association between sleep duration and cancer mortality in men in the multivariable model in the current study is explained entirely by the included covariates that abrogated the significant associations in the minimally adjusted model.…”
Section: Discussionmentioning
confidence: 94%
“…In another study, which examined retired individuals only, a U‐shaped association was also found (Akerstedt et al, 2021). Finally, another study uncovered a U‐shaped association in both young and old groups (Svensson et al, 2020). However, the young group in that study used 40 years as the lowest age (rather than the 18 years used in the present study); thus, young adults were excluded.…”
Section: Discussionmentioning
confidence: 97%
“…The U‐shaped associations have been significant, although rather modest, in most meta‐analyses, despite the original studies being age adjusted in the basic model (Cappuccio et al, 2010; da Silva et al, 2016; Yin et al, 2017; Liu et al, 2017; Ren et al, 2020). In some studies that were stratified by age, a U‐shaped association between sleep duration and mortality was found in the older group, but not in the younger one (Gangwisch et al, 2008; Yeo et al, 2013), as well as in both groups (Svensson et al, 2020). However, the cut‐off for age was only 50 or 60 years, respectively, in those studies, that is, the older groups in those studies were rather young.…”
Section: Introductionmentioning
confidence: 99%
“…The Government of Japan recommends that the working middle‐aged individuals sleep “as long as they can.” 13 The 2018 National Health and Nutrition Survey found that, among individuals aged 20 years and above, 36.0% of men and 39.6% of women reported <6 hours of daily sleep 14 . Individual Japanese cohort studies found no associations between sleep duration and cancer mortality 15,16 and incidence 17 . However, one study found that short sleep was associated with increased cancer mortality in men but not women 18 .…”
Section: Introductionmentioning
confidence: 99%